2013
DOI: 10.1007/s13197-013-1099-3
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and characterization of pectin methylesterase from Alyanak apricot (Prunus armeniaca L)

Abstract: This study was carried out to determine some of the biochemical properties of pectin methylesterase (PME) from Alyanak apricot which is an important variety grown in Malatya region of Turkey. The enzyme had high activity in a pH range of 7.0-8.0 with the maximal activity occurring at pH 7.5. However, the enzyme activity at high and low pH values was very low. The optimum temperature for maximal PME activity was found to be 60°C. The activity of PME has been enhanced by NaCl, particularly at 0.15 M. K m and V m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It was observed that juice cloud stability is directly influenced by pH. The observed trend cannot be explained solely by PME activity, since sedimentation occurred more slowly in the less acidic juices where PME was expected to be most active [21]. This same trend has been observed to varying degrees depending on juice batches (data not shown).…”
Section: Ppo Pod and Pme Activities Of Individual Components In Thementioning
confidence: 84%
“…It was observed that juice cloud stability is directly influenced by pH. The observed trend cannot be explained solely by PME activity, since sedimentation occurred more slowly in the less acidic juices where PME was expected to be most active [21]. This same trend has been observed to varying degrees depending on juice batches (data not shown).…”
Section: Ppo Pod and Pme Activities Of Individual Components In Thementioning
confidence: 84%
“…As expected, the findings were parallel to PME activity, and 50.8‐μm film bags containing 15% Fe powder sachets recorded significantly lowest PG activities of only 6.6%, 9.8%, 14.2%, and 18.5% throughout the storage durations (30, 60, 90, and 120 d, respectively). This behavior signifies that that enzymes (PME and PG) actively participate in fruit softening and leads to onset of senescence, which is pre‐expected 46 . PME activity results in removal of methyl esters from galacturonic acid chain, thus making pectin more susceptible to action of PG, which then initiates linear breakdown of pectin molecules resulting in softening of fruits 47…”
Section: Resultsmentioning
confidence: 97%
“…Pectin methylesterase (PME) is involved in the loss of firmness by demethylating pectin (Figure 1), making it sensitive to the activity of PGs. Ünal and Şener [20] studied the biochemical properties of MSY in Alyanak apricots (an important variety in the Malatya region of Turkey). This PME has a high activity for a pH between 7.0 and 8.0 with a maximum activity at pH 7.5, knowing that the pH of an apricot fruit for example generally varies between 3.3 and 4.0.…”
Section: Pectin Methylesterasementioning
confidence: 99%